Progress through high school : a study of senior secondary schooling in New South Wales - Ainley, John, 1945- (Australian Council for Educational Research, 1992)
Introduction. Perspectives from previous studies. The study. The middle secondary years. School differences in year 9. Staying at high school. School holding power. The senior secondary years. Beyond school. Conclusions.